2011
DOI: 10.4239/wjd.v2.i2.24
|View full text |Cite
|
Sign up to set email alerts
|

New insights in diabetic foot infection

Abstract: Foot ulcers are common in diabetic patients, have a cumulative lifetime incidence rate as high as 25% and frequently become infected. The spread of infection to soft tissue and bone is a major causal factor for lower-limb amputation. For this reason, early diagnosis and appropriate treatment are essential, including treatment which is both local (of the foot) and systemic (metabolic), and this requires coordination by a multidisciplinary team. Optimal treatment also often involves extensive surgical debridemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 61 publications
6
91
1
2
Order By: Relevance
“…20 Phenytoin has been widely used in the treatment of epilepsy since 1937. It has been used for the treatment of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…20 Phenytoin has been widely used in the treatment of epilepsy since 1937. It has been used for the treatment of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since these wounds tend to be colonized by a range of microorganisms, definition of infection should be guided by clinical criteria and not by simply demonstrating growth of microorganisms in culture. 4,9,11 A critical value for colonizing bacteria of around 100,000 colonies has been proposed; however, it has also been demonstrated that more virulent pathogens, even when in smaller numbers, have greater potential to damage tissues than less virulent strains, even when colonizing the same tissues. 12,13 The objective is that by taking a sample from the wound, the bacteria that is probably responsible for the infection will be identified, rather than to achieve a simple proof of presence or absence of infection.…”
Section: 10mentioning
confidence: 99%
“…9 Serological markers, such as tests of inflammatory activity and white blood counts, tend to offer low sensitivity and specificity. 4 However, even though clinical features indicating local infection may present in a subtle form, they still remain the best method for diagnosing infection in the diabetic foot and can also be used to quantify the degree of infection, as proposed by the International Working Group on the Diabetic Foot (IWGDF).…”
Section: 8mentioning
confidence: 99%
See 2 more Smart Citations